O DESENVOLVIMENTO COGNITIVO EM CRIANÇAS DE ESCOLA - DRUGG, ANGELA M. S.; SOUZA, FABIANA B. D.; NODARI, JOSÉ M.; NODARI, LALA C. L.; RUFINO, SOLANGE M.; FENGLER, SONIA A. D. C. (Salão do Conhecimento, 2013)
Resumo